Human ZBP1 induces cell death‐independent inflammatory signaling via RIPK3 and RIPK1. (21st October 2022) - Peng, Ruoshi; Wang, Chris Kedong; Wang‐Kan, Xuan; Idorn, Manja; Kjær, Majken; Zhou, Felix Y; Fiil, Berthe Katrine; Timmermann, Frederik; Orozco, Susana L; McCarthy, Julia; Leung, Carol S; Lu, Xin; et al.
Abstract: ZBP1 is an interferon‐induced cytosolic nucleic acid sensor that facilitates antiviral responses via RIPK3. Although ZBP1‐mediated programmed cell death is widely described, whether and how it promotes inflammatory signaling is unclear. Here, we report a ZBP1‐induced inflammatory signaling pathway mediated by K63‐ and M1‐linked ubiquitin chains, which depends on RIPK1 and RIPK3 as scaffolds independently of cell death. In human HT29 cells, ZBP1 associated with RIPK1 and RIPK3 as well as ubiquitin ligases cIAP1 and LUBAC. ZBP1‐induced K63‐ and M1‐linked ubiquitination of RIPK1 and ZBP1 to promote TAK1‐ and IKK‐mediated inflammatory signaling and cytokine production. Inhibition of caspase activity suppressed ZBP1‐induced cell death but enhanced cytokine production in a RIPK1‐ and RIPK3 kinase activity‐dependent manner. Lastly, we provide evidence that ZBP1 signaling contributes to SARS‐CoV‐2‐induced cytokine production. Taken together, we describe a ZBP1‐RIPK3‐RIPK1‐mediated inflammatory signaling pathway relayed by the scaffolding role of RIPKs and regulated by caspases, which may induce inflammation when ZBP1 is activated below the threshold needed to trigger a cell death response. Synopsis: ZBP1 is a nucleic acid sensor that induces cell death via RIPK3. This study describes a ZBP1‐induced inflammatory signaling pathway that is independent of cell death and is mediated by non‐degradative ubiquitin chains, and RIPK1 and RIPK3 as scaffolds. ZBP1 stimulates signaling and cytokine production independently of cell death. ZBP1 signaling relies on the scaffolding functions of RIPK3 and RIPK1, but not their kinase activities. ZBP1 signaling is mediated by K63‐ and M1‐linked ubiquitin chains generated by cIAPs and LUBAC. ZBP1 contributes to cytokine production after SARS‐CoV‐2 infection. Abstract : ZBP1 is a nucleic acid sensor that induces cell death via RIPK3. This study describes a ZBP1‐induced inflammatory signaling pathway that is independent of cell death and is mediated by non‐degradative ubiquitin chains, and RIPK1 and RIPK3 as scaffolds.